PROFIL TOKOH DALAM NOVEL KUHAPUS NAMAMU DENGAN NAMA-NYA KARYA TAUFIQURRAHMAN AL-AZIZY - Iman, Abdhol; Tamsin, Andria Catri; Zulfadhli, Zulfadhli (Universitas Negeri Padang, 2013)
This article was written to describe character ofÂ profile in novel Kuhapus Namamu dengan Nama-Nya by Taufiqurrahman Al-Azizy. The data of the research was novel component profile of character novel Kuhapus Namamu dengan Nama-Nya by Taufiqurrahman Al-Azizy. The source of the data research novel Kuhapus Namamu dengan Nama-Nya by Taufiqurrahman Al-Azizy. The method used in this research was descriptive method. Research finding profile of characters in novel Kuhapus Namamu dengan Nama-Nya by Taufiqurrahman Al-Azizy that consist of seven characters. First, as a main character Naufal has a view or life, responsibility, justness, strength to face suffering, and beauty. And six supporting actris are Naura is lovely, responsibility, and unpatien to face suffering. Saâ€™di is responsibility, and describes the beauty of woman. Abah and Umi are responsible parents, and Mr. Seno has responsible to other people and god.